INTELLIGENCE DISCOURSE IN EDUCATION: INTEGRATION OF IQ, EQ, AND SQ - Nur Fadillah, Ega; Nuraningsih (UIN Sunan Gunung Djati Bandung, 2024)
This research aims to conduct a discourse on the concepts of IQ (Intelligence Quotient), EQ (Emotional Quotient), SQ (Spiritual Quotient) and the role of each intelligence in shaping a successful person in Indonesia. This research uses a qualitative approach with content analysis. This approach is carried out by searching and analysing relevant theoretical sources to gain a deep understanding of the research topic. The content analysis involves systematic analysis of textual, visual, or audio content to identify patterns, themes, or meanings within the data. This approach is important in developing quality research and providing a holistic understanding of the topic under research. The results of this research show that in the discourse on intelligence IQ, EQ, and SQ have their own differences and roles. IQ is likened to